Synthesis of 2-substituted 6-(5-oxo-1-phenylpyrrolidin-3-yl)pyrimidin-4(3H)-ones - Groselj, Uros; Dahmann, Georg; Stanovnik, Branko; Svete, Jurij (European Journal of Chemistry, 2013)
2-Substituted 6-(5-oxo-1-phenylpyrrolidin-3-yl)pyrimidin-4(3H)-ones were synthesized in three steps from itaconic acid derivatives via cyclization with primary amines followed by Masamune-Claisen condensation, and cyclization of the newly formed β-keto esters with amidines. Preparation and/or isolation of β-keto esters with polar N-substituents failed, but the corresponding final products were obtained in a different way. 6-(1-(3-Hydroxypropyl)-5-oxopyrrolidin-3-yl)-2-phenylpyrimidin-4(3H)-one was obtained by hydrogenolytic o-deprotection of its o-benzyl derivative. Depending on reaction conditions, further mesylation of 6-(1-(3-(benzyloxy)propyl)-5-oxopyrrolidin-3-yl)-2-phenylpyrimidin-4(3H)-one followed by treatment with pyrrolidine gave either the monoaminated- or the diaminated product. The structures of novel compounds were determined by NMR.